2018
DOI: 10.3389/fpsyt.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Systematic Reviews on Forensic Psychiatric Care: A Systematic Review Identifying Knowledge Gaps

Abstract: Background: Forensic psychiatric care treats mentally disordered offenders who suffer mainly from psychotic disorders, although comorbidities such as personality disorders, neurodevelopmental disorders, and substance abuse are common. A large proportion of these patients have committed violent crimes. Their care is involuntary, and their caregivers' mission is complex: not only to rehabilitate the patient, but also to consider their risk for reoffending and their risk to society. The objective of this overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…The professional skills and interventions speci c to preventing and managing violence and aggression in hospital are increasingly the subject of development and training, but research in this area is sparse. Recent Cochrane reviews and systematic reviews found no studies that met inclusion criteria, much evidence for adverse effects and a lack of focus upon non-pharmacological methods for containment of violence or self-harm in people with serious mental illness (3,4,5).…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The professional skills and interventions speci c to preventing and managing violence and aggression in hospital are increasingly the subject of development and training, but research in this area is sparse. Recent Cochrane reviews and systematic reviews found no studies that met inclusion criteria, much evidence for adverse effects and a lack of focus upon non-pharmacological methods for containment of violence or self-harm in people with serious mental illness (3,4,5).…”
Section: Rationalementioning
confidence: 99%
“…The interventions used to prevent violence are notoriously lacking in the sort of scienti c evidence required to meet the standards of Cochrane reviews or meta-analysis (3,4,5). Interventions such as seclusion and restraint are commonly condemned from the point of view of principled human rights.…”
Section: Generalisabilitymentioning
confidence: 99%
“…A recent review (13) emphasizes the value of clozapine in the treatment of violent and aggressive behaviors also in a forensic population. Another recent study (14) identified two previously published systematic reviews, which in part addressed the effects of pharmacological interventions within forensic psychiatry (15,16), showing that only a few primary studies had been published, all of which were assessed as being at high risk of bias. However, the reports had methodological limitations and could potentially have resulted in relevant records having been overlooked.…”
Section: Introduction Rationalementioning
confidence: 99%
“…Despite these common denominators, forensic patients are a heterogeneous group in terms of the details of their offense history, psychopathology and risk factors (3). That notwithstanding, in most jurisdictions, forensic psychiatric patients suffer primarily from disorders with psychotic symptomatology, but comorbidities are very common, especially personality disorders, neurodevelopmental disorders and substance-related disorders (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%